Penerapan Metode Time Charter Party Pada Sistem Informasi Penyewaan Alat Camping Berbasis Web - Andi Hidayat; Ucuk Darusalam (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Sinar Adventure Store is a shop that provides camping equipment, this store has many customers who want to rent camping equipment such as tents, carril bags, stoves and sling bags. But the camping equipment rental transaction at this shop still uses the conventional process, so there are still many errors that occur in writing information and data reports on this camping equipment rental. This is the author's reference in designing a web-based camping equipment rental information system, with HTML, CSS, and PHP programming languages as the database. This system is designed using the waterfall method and the system follows the flow of the Time Charter Party method. In data processing, such as recording rental transaction data, it is still stored in a ledger storage media so that data security is not guaranteed because there is no more searching for camping equipment data at the Sinar Adventure Store who still has to wait a long time because they have to find one data person in the books. The purpose of creating this rental system is to overcome the problems that are currently happening at the Sinar Adventure Store store. The results of this study are to provide convenience in the processing of camping equipment data at the Sinar Adventure Store store such as admin data, data rental, ordering, checkout and to simplify the data search process in addition to having a more effective and larger storage media.